Increased para-aortic adipose tissue on echocardiography may closely be related with fragmented QRS (Colombia Medica, 2024)
Background: The association of fragmented QRS (fQRS) with many cardiac pathologies such as cardiac fibrosis has been described previously. Paraaortic adipose tissue (PAT) is thought to be associated with many cardiac diseases and there is only one publication on its echocardiographic evaluation. This study aims to describe the possible relationship between fQRS and PAT.Methods: Patients presenting to the cardiology outpatient clinic were evaluated for inclusion in the study. Presence of additional R' wave or notching/splitting of S wave in two contiguous ECG leads was defined as fragmented QRS (fQRS) and patients were divided into two groups according to fQRS status on ECG. The hypoechoic space in front of the ascending aorta was considered as PAT in the parasternal long-axis view. The medical history and routine laboratory parameters of the participants were recorded. Univariate and multivariate binary regression analysis was used to determine the relationship between PAT and fQRS.Results:A total of 221 patients were enrolled and divided into two groups according to fQRS status. PAT was significantly higher in the fQRS group [9.2mm (7.1/12.3) vs 6.8mm (1.2/10.9), p=0.001]. Univariate analysis showed significant association between fragmented QRS and PAT size (OR 1.122, p= 0.001).  Binary regression analysis revealed an independent and strong association between aortic size (OR 1.4, CI 1.012-1.938, p=0.042), paraaortic adipose tissue (OR 1.483, CI 1.084-2.029, p=0.014) and fragmented QRS.Conclusions: The presence of fQRS is associated with PAT, a newly defined parameter in echocardiography.